Praktik pemasaran berjenjang Halal Network Internasional Herbal Penawar Alwahida Indonesia (HNI HPAI) Jakarta ditinjau dari aspek hukum ekonomi syariah - Ardabili, Dadad (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
This study aims to explore and analyze the compensation system and networking model in the HNI HPAI business. So far, HNI HPAI is considered by some people to contain usury and money games in its practices. The opinions of Middle Eastern scholars and fatwas regarding the prohibition of MLM are the reasons for doubts about the HNI HPAI multilevel marketing business. The form of this research is library research with a comparative descriptive method through the fiqh and ushūl al-fiqh approaches. The triangulation method is also used to confirm the validity of the data sources and the results of interview research with related parties. The primary data sources used are data from documents and interviews related to the problem being studied. While secondary data sources are obtained from literature in the form of library data, both print media, research journals, DSN MUI Fatwas, and internet media. The results of the study show that some of the contracts used are the murābahah, wakālah bi al ujrah, and juʻālah contracts. In the HNI HPAI business, there were also no usury practices and money games or pyramid schemes. It can be concluded that HNI HPAI's multilevel marketing practices are in accordance with the principles of Islamic economic law, namely the fatwa issued by the DSN MUI.